Waqf as a Sustainable Fiscal Instrument in Islamic Economics: A Disaster Management Perspective - Mochammad Ae Dunur'aeni; Fadllurrohman Fadllurrohman; Hera Purwanti; Aris Puji Purwatiningsih; Ozioma Victoria Uchime (Mawaddah: Jurnal Hukum Keluarga Islam, 2026)
This study aims to analyze the role of waqf as an instrument to support fiscal policy in the Islamic economic system, especially in disaster management. The approach used is descriptive qualitative with secondary data sources in the form of classical and contemporary literature in sharia economic law. The data were analyzed thematically to identify the distribution mechanism and implementation of waqf in the disaster management cycle. The results of the study show that waqf is an instrument of Islamic philanthropy that has significant potential as a source of public income other than zakat, infaq, and alms. In contrast to zakat which is mandatory, waqf is voluntary but has a sustainability character through the management of productive assets. The status of waqf is included in the category of al-milkiyyah al-'ammah, although in certain practices it can be al-expert. In the context of disaster management, waqf can be implemented in three main stages, namely mitigation (reforestation and environmental conservation), emergency response (provision of shelter, health services), and rehabilitation (reconstruction of public facilities such as hospitals, madrasas, and mosques). These findings confirm that waqf has a strategic position as a sustainable alternative fiscal instrument in strengthening sharia-based socio-economic resilience. Therefore, it is recommended that there be the integration of waqf in national fiscal policy, the strengthening of nadzir institutions, and innovations in productive waqf management to be optimal in supporting an effective and sustainable disaster management system.